2017
DOI: 10.3390/en10050638
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Foraging Reinforcement Learning for Risk-Based Economic Dispatch via Knowledge Transfer

Abstract: This paper proposes a novel bacteria foraging reinforcement learning with knowledge transfer method for risk-based economic dispatch, in which the economic dispatch is integrated with risk assessment theory to represent the uncertainties of active power demand and contingencies during power system operations. Moreover, a multi-agent collaboration is employed to accelerate the convergence of knowledge matrix, which is decomposed into several lower dimension sub-matrices via a knowledge extension, thus the curse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In terms of risk dispatching, the RL algorithm can be used to solve risk assessment issues for economic dispatch (ED). For example, Han et al demonstrated an RL‐based transfer BFO (TBFO) knowledge model, which can address the fast risk‐based ED optimization issues in large‐scale complex power grids. Concretely speaking, in this knowledge model, a kind of heuristic BFO algorithm was combined with the try‐error mechanism of Q‐learning.…”
Section: Reinforcement Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of risk dispatching, the RL algorithm can be used to solve risk assessment issues for economic dispatch (ED). For example, Han et al demonstrated an RL‐based transfer BFO (TBFO) knowledge model, which can address the fast risk‐based ED optimization issues in large‐scale complex power grids. Concretely speaking, in this knowledge model, a kind of heuristic BFO algorithm was combined with the try‐error mechanism of Q‐learning.…”
Section: Reinforcement Learningmentioning
confidence: 99%
“…The methods to solve such issues not only include conventional optimization methods such as the interior‐point algorithm but also include the probabilities achieved search‐based heuristic SI algorithms such as GA, PSO, ABC, and QGA . In the solution process, TL, a learning framework that has been a growing concern and has been widely investigated in recent years, aims to apply experience (ie, knowledge or strategy) and the results learned previously in the auxiliary field to a similar but different target domain based on task similarity and to reuse the existing experience to accelerate the learning speed of the new tasks and thus improve the efficiency with which the new tasks can be learned …”
Section: Transfer Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…In applications involving the online control or dispatch of power systems, reinforcement learning (RL) methods have exhibited remarkable capabilities for performing online calculations [21][22][23]. RL is based on the concept of trial and error and explicitly considers the problem of a goal-directed agent interacting with an uncertain environment [24].…”
Section: Introductionmentioning
confidence: 99%